From Welfare to Human Flourishing: Maqasid al-Shariah as the Nexus of Islamic Social Finance, Da'wah, and Sustainable Development - Murjanatu Yusuf; Adamu Abubakar Muhammad; Yusuf Isa Sawaba; Maryam Babani Muhammad; Isma’il Iliyasu Danladi (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2026)
In recent years, there has been increased interest in the fields of Islamic Social Finance (ISF) and Sustainable Development. However, these fields have been considered separately, lacking an integrated approach that emphasizes the role of Da'wah as a tool for transformative change for the ethical and social betterment of society. Such fragmentation ignores the broader perspective of Maqasid al-Shariah which aspires not only for material progress, but also for the moral, social and complete human flourishing (falah). This article aims to utilize the Maqasid al-Shariah framework as the normative and strategic tool which integrates Islamic Social Finance, Da'wah, and Sustainable Development as a unified model for development.  Adopting a qualitative doctrinal methodology utilizing thematic analysis of the Qur’an, Sunnah, classic juristic and contemporary literatures, this study analyzes how zakah, waqf, sadaqah, qard al-hasan, Da'wah institutions and sustainable development practices play complementary roles in achieving Maqasid al-Shariah. This study argued that Islamic Social Finance should not be understood merely as poverty alleviation but rather as a catalyst for change which works alongside Da’wah as interconnected mechanisms for enhancing human dignity, social justice, ethical reform and social well-being for human beings and the protection of the environment for future generation. The Maqasid-based conceptual framework of Islamic development is presented for policy makers to govern and manage institution towards preserving and protecting: the religion, the life, the intellect, the lineage, the wealth, the dignity, the justice, and the environment. The paper conclude that an integration of ethical transformation and Islamic social Finance under the canopy of the Maqasid al-Shariah, would represent a more holistic approach to sustainable development than models solely focused on economic progress, and thus contributing to the ongoing debate on the Islamic development theory and practice.